Soybean molasses as feedstock for sustainable generation of biomethane using high-rate anaerobic reactor - Rodrigues, Brenda Clara Gomes [UNESP]; De Mello, Bruna Sampaio [UNESP]; Gonsales Da Costa Araujo, Maria Lucia [UNESP]; Ribeiro Da Silva, Gustavo Henrique [UNESP]; Sarti, Arnaldo [UNESP] (Elsevier, 2021)
Anaerobic digestion of agro-industrial wastes is an environmentally friendly green biotechnology of significant interest in order to facilitate sustainable development of bioenergy production. Thus, it becomes important to invest in management processes for agro-industrial wastes, particularly low-cost ones. In this paper, the main purposes were to investigate the performance of a high-rate reactor and biogas generation potential by anaerobic digestion of soybean molasses, which is a viscous liquid of brown color obtained as a byproduct from processing of the soy protein industry concentrate. A lab-scale up-flow anaerobic sludge blanket reactor (UASB reactor), with a total volume of 12 L, was operated at six different organic loading rates (OLR) ranging from 0.28 to 6.98 kgCOD m-3 d-1 (COD of 500-4000 mg L-1). The reactor was fed with soybean molasses for 134 days and maintained under mesophilic conditions. Different values were tested for the hydraulic retention time (HRT of 48, 24 and 12 h). After the fast startup period (52 days), the mean values of removal efficiencies (CODTotal) ranged from 70% to 83% in all experimental periods. In a UASB reactor, a higher organic loading rate of 6.98 kgCOD m-3 d-1 could be tolerated, but it resulted in a lower biomethane yield of 356.1 mLCH4 gCOD-1. In addition, for all the tested COD concentrations and HRT, high concentrations of methane in the biogas were obtained from 72.5% to 82.1%. Based on the experimental results, it can be verified that this high-rate anaerobic configuration can be used for the biomethane generation of soybean molasses and the produced effluent can be reutilized in the dilution of soybean molasses for reactor feed.
Keywords: Anaerobic digestion; Biogas; Methane; Soybean molasses; UASB reactor